Pengembangan Sistem Keselamatan Dan Peringatan Bahaya Dini Pada Aplikasi Sistem Navigasi Dan Pengujian Manuver Kapal Untuk Kapal Nelayan Tradisional Di Brondong Lamongan Jawa Timur Berbasis Internet Of Things - Herijono, Boedi; Leonard, Rikky; Toto Wibowo, Alvalo; Pristovani Riananda, Dimas; Ratna Kusuma Mayang Sari, Dyah (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Safety Issues and Early Warning for Traditional Fishermen While Sailing in Brondong Lamongan, East Java. The purpose of the Community Service activity is that with the Simple tool, it is hoped that traditional fishermen in Brondong Lamongan, East Java will be guaranteed safety while sailing. The method applied is a participatory approach, which actively involves the community in every stage of the activity, from planning, implementation, to evaluation. Active participation from the community is very important to ensure the success and sustainability of the program, because the community has in-depth local knowledge about the potential and problems that exist in their area. The location of this Community Service is in the Brondong Lamongan Fishermen's Association, East Java. Based on the results of the Community Service, it can implement the Simple Tool as a Safety System and Early Warning for Traditional Fishermen While Sailing in Brondong Lamongan, East Java, so that it can be used to increase fishing productivity and safety for traditional fishermen which is a problem for these traditional fishermen.